English as a lingua franca in the Vietnamese hotel industry: Communicative strategies and their implications for vocational education - Vu, Thi Hong Van (Curtin University, 2015)
The strategies employed by Vietnamese hotel staff in their communication in English with foreign guests were examined. Communicative strategies were used to ensure the success of each interaction. The study also examined the extent to which the use of these strategies is fostered by the coursework hospitality students undertake. A lack of alignment between the language presented in the textbooks and the language used in an authentic hotel setting was identified.